Indonesia Reconstructing the Qur'anic Interpretation of the Law of Inheritance: Finding Gender Justice in the Passage of the Times - Rohman, Baeti (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
Quranic interpretation is an essential bridge for understanding divine messages amid the dynamics of humanity. This article aims to examine the urgency and methodological approach in reconstructing Quranic interpretation, focusing on Q.S. An-Nisa '[4]: 11, which literally regulates the 2:1 inheritance distribution between men and women. Using a historical-critical approach and philosophical hermeneutics, this study applies Fazlur Rahman's interpretation model with the “double movement” method and Nasr Hamid Abu Zayd's concept of implicit meaning (dalālat al-maskūt ʿanh). This reconstruction does not aim to remove the authenticity of revelation, but rather to explore the universal principle of the Qur'an, namely justice, which is then reformulated in the context of modern society that upholds gender equality and human rights. The results of the study show that openness to contextual and multidisciplinary readings can enrich the tradition of interpretation and present a transformative and relevant Islam. The reconstruction of interpretation on the issue of inheritance is a strategic step to bridge the divine text with the needs of social justice today.